Analysis of image types, compression techniques and performance assessment metrics : A review. Issue 3 (3rd April 2022) - Garg, Garima; Kumar, Raman
Abstract: The rapid advancement of digital technology has created a demand for improved compression methods. Image compression is data compression applied to digital images. The goal is to eliminate picture data redundancy in order to store or transfer data efficiently. When a picture is compressed at low bitrates, the image fidelity is lost. Images can be compressed in several ways. This paper reviews image kinds and compression strategies. All type of images and the factors by which one can identify the performance assessment of images are described in this paper.